Regeneration efficiency based on genotype, culture condition and growth regulators of eggplant (Solanum melongena L.) - Muktadir, Md Abdul; Habib, Muhammad Ashraful; Mian, Md Abdul Khaleque; Akhond, Md Abdullah Yousuf (Agriculture and Natural Resources, 2016)
Several experiments were carried out to establish an efficient regenerating protocol for cultivated eggplant varieties. Among the five varieties cultured on Murashige and Skoog (MS) medium with free plant growth regulator (PGR), Nayantara performed better considering the number of shoots/explant (2.48). Considering explant types and culture conditions, better performance was observed (3.68 shoots/ explant) when seed germination in the dark was proceeded by bottom hypocotyl segments cultured under dark conditions. A higher rate of shoot regeneration was observed in Nayantara when cultured in Zeatin Riboside (ZR) and Thidizuron (TDZ) supplemented MS medium. The highest number of shoots per explant was produced on MS medium supplemented with 2.0 mg/L ZR and 0.1 mg/L indole acetic acid (6.65 shoots/explant). Proliferation and elongation of the regenerated shoots were obtained in the MS medium with free PGR. The best rooting performance was observed in MS medium supplemented with 2.0 mg/L indole butyric acid. Plantlets with well developed roots and shoots were successfully transferred to soil.